Coping strategies and solution perspectives of the educational community against bullying (bullying) in urban Lima 2014-2015 - Marchena Cárdenas, Carlos Efraín (2019)
Bullying is a psychosocial problem at a national level as in other countries, which affects many adolescents and also children. The harassment itself is when the harassment is repetitive and disrupts the normal development of the school. The ethnographic approach was used, based on the naturalistic observation of the school environment. In-depth interviews, focus groups and systematic observations were applied. The general objective was to describe school bullying, coping strategies and the solution prospects used by the educational community (parents, teachers and students) against it. The strategies of confrontation to harassment on the part of the educational authorities were those of minimization and avoidance of this problematic. Among the students, distance and avoidance prevailed as coping strategies. The parents considered as a strategic priority, the control and education granted in the educational institutions. The students proposed as solutions to harassment, the greater approach of their families and teachers. The prospects of students’ solution to the harassment were more numerous than those of teachers and parents.